Effects of hemodilution on coagulation function during prolonged hypotensive resuscitation in a porcine model of severe hemorrhagic shock - Clifford G Morgan; Leslie E Neidert; Emily N Hathaway; Sylvain Cardin; Jacob J Glaser; Peter J Hemond; Michael M Tiller (Trauma Surgery & Acute Care Open)
Background Although hemorrhage remains the leading cause of survivable death in casualties, modern conflicts are becoming more austere limiting available resources to include resuscitation products. With limited resources also comes prolonged evacuation time, leaving suboptimal prehospital field care conditions. When blood products are limited or unavailable, crystalloid becomes the resuscitation fluid of choice. However, there is concern of continuous crystalloid infusion during a prolonged period to achieve hemodynamic stability for a patient. This study evaluates the effect of hemodilution from a 6-hour prehospital hypotensive phase on coagulation in a porcine model of severe hemorrhagic shock.Methods Adult male swine (n=5/group) were randomized into three experimental groups. Non-shock (NS)/normotensive did not undergo injury and were controls. NS/permissive hypotensive (PH) was bled to the PH target of systolic blood pressure (SBP) 85±5 mm Hg for 6 hours of prolonged field care (PFC) with SBP maintained via crystalloid, then recovered. Experimental group underwent controlled hemorrhage to mean arterial pressure 30 mm Hg until decompensation (Decomp/PH), followed by PH resuscitation with crystalloid for 6 hours. Hemorrhaged animals were then resuscitated with whole blood and recovered. Blood samples were collected at certain time points for analysis of complete blood counts, coagulation function, and inflammation.Results Throughout the 6-hour PFC, hematocrit, hemoglobin, and platelets showed significant decreases over time in the Decomp/PH group, indicating hemodilution, compared with the other groups. However, this was corrected with whole blood resuscitation. Despite the appearance of hemodilution, coagulation and perfusion parameters were not severely compromised.Conclusions Although significant hemodilution occurred, there was minimal impact on coagulation and endothelial function. This suggests that it is possible to maintain the SBP target to preserve perfusion of vital organs at a hemodilution threshold in resource-constrained environments. Future studies should address therapeutics that can mitigate potential hemodilutional effects such as lack of fibrinogen or platelets.Level of evidence Not applicable—Basic Animal Research.